Hybridizing Real and Virtual Worlds: A Workflow-Based Approach Using 3D Scanners and Printers - Franco, Guilherme C.; Nascimento, Hugo A. D.; Salles, Laurita R.; G. Filho, Arlindo R.; Carvalho, Sergio T.; Berretta, Luciana O. (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR), 2025)
Extended Reality (XR) is an immersive technology that integrates physical and digital environments. XR applications are being increasingly adopted across various sectors, including education, healthcare, entertainment, and industry. These applications leverage diverse interaction modalities, including gestures, voice commands, haptic feedback, and motion-based interfaces, allowing users to manipulate virtual objects, navigate simulated environments, and interact with digital content. The choice of interaction depends directly on factors such as the level of immersion, available technological resources, and the physical conditions of the environment. To achieve a convincing sense of immersion, virtual objects and environments must exhibit visual and geometric properties consistent with the physical world. This work in progress investigates an integrated model that combines tools and techniques for digitizing real objects and manufacturing their virtual counterparts. The research assesses both the quality of the generated models and their suitability for use in immersive XR environments. The proposed workflow comprises two independent initial stages: (i) the virtualization of physical objects and (ii) the manufacturing of objects represented in the Metaverse.